Quali-quant analysis of the statistical content in Italian primary school general books. - Clerici, Renata; Gola, Giancarlo; Cisco, Emanuela (International Journal of Multiple Research Approaches, 2013)
The conjoint use of multi-method techniques puts into action the methodological triangulation that can produce interesting results about the evaluation of textbook contents. In this perspective we analyze a random sample of fourth- and fifth-grade Italian primary mathematics general books. By using a mixed methods research approach, we conducted a content analysis of these textbooks, starting from an ex ante conceptual grid that allowed us to observe the contents of the pages dedicated to the subject. Initially, we used the computer software package ATLAS.ti to describe accurately the relationships between structural and content aspects. The codes obtained from the computerized content analysis were transformed into a matrix of statistical data, in which the cases and the variables (each category) were analyzed via the PASW Statistics package. The application of canonical non-linear correlation analysis to the set of these textbook characteristics (in particular statistical graphic representation) yielded a content typology.